2012
DOI: 10.1007/s10439-011-0502-3
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of Blood Damage in the Hinge Area of Aortic Bileaflet Mechanical Heart Valves During the Leakage Phase

Abstract: Previous experimental and numerical blood studies have shown that high shear stress levels, long exposure times to these shear stresses, and flow recirculation promote thromboembolism. Artificial heart valves, in particular bileaflet mechanical heart valves (BMHVs), are prone to developing thromboembolic complications. These complications often form at the hinge regions of BMHVs and the associated geometry has been shown to affect the local flow dynamics and the associated thrombus formation. However, to date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…The authors have demonstrated in previous studies that LBM in combination with the EBF method is able to accurately quantify platelet damage in BMHV flows on a smaller scale in the hinges when compared with blood damage experiments (Wu et al 2011;Yun et al 2012). The LBM-EBF method can now be included to accurately quantify platelet damage in pulsatile flows throughout the entire BMHV geometry in future studies across varying physiologic conditions.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors have demonstrated in previous studies that LBM in combination with the EBF method is able to accurately quantify platelet damage in BMHV flows on a smaller scale in the hinges when compared with blood damage experiments (Wu et al 2011;Yun et al 2012). The LBM-EBF method can now be included to accurately quantify platelet damage in pulsatile flows throughout the entire BMHV geometry in future studies across varying physiologic conditions.…”
Section: Resultsmentioning
confidence: 89%
“…This would increase the chances of thromboembolic complications incurred in diastolic flows, beyond those complications already known to occur in the hinge regions. Using the platelet damage quantification method with LBM-external boundary force (EBF) (Wu et al 2011;Yun et al 2012), these high-risk regions can be further analysed in future simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of biomechanical platelet activation have typically modeled platelets as either infinitesimal [22,23,25,[31][32][33] or finite-sized [26,[34][35][36][37][38] particles. In either case, Lagrangian particle tracking of the position and stress histories of individual platelet surrogates in the flow is used.…”
Section: Introductionmentioning
confidence: 99%
“…De Wachter and Verdonck, 2002;Yun et al, 2012). However, still there is a lack of reliable mathematical model to correlate differential shear stress and the exposure time to damage experienced by blood cells.…”
Section: Discussionmentioning
confidence: 99%